Researching multiple publics through latent profile analysis: Similarities and differences in science and technology attitudes in China, Japan, South Korea and the United States. (February 2019) - Pullman, Ashley; Chen, Michelle Y.; Zou, Danjie; Hives, Benjamin A.; Liu, Yan
How science and technology attitudes vary across the United States, China, South Korea and Japan – all of which top Bloomberg's list of high-tech centralization – is explored through data from the sixth wave of the World Values Survey (2010–2014). The following study examines the presence of different types of attitudinal groups using latent profile analysis. Not only do unique attitudinal groups exist in each country, but each group is uniquely influenced by select demographic characteristics, including education, age, gender, religiosity, employment status and individual interaction with technology. The findings provide insight into public attitudes towards science and technology across social and cultural contexts and generate nuanced understandings of similar and different attitudinal groups in East Asia and the United States.